ILOKUSI DALAM WACANA KAOS OBLONG JOGER: SEBUAH ANALISIS PRAGMATIK - Adhitama, Agus Surya (Humanis, 2013)
There are many ways to create a communication and one of them is through the media of clothes. This research was conducted in the field of clothes since it has wide scope and its function is freer rather than the other media. There are two aims of the study. The first is to find out the types of illocutionary acts. The second is to explain the functions of those types of illocutionary acts. Recording to the problems of the study, there are two theories were used in this study, they are the theory of taxonomy of illocutionary acts proposed by Searle and the theory of context proposed by Yule. The result of this study shows that there are five types of illocutionary acts and there are eleven functions of those types found through the text in Joger’s clothes.
Keywords: text, type, function